Developments in Environmental Regulation Risk based regulation in the UK and Europe (Palgrave Studies in Environmental Policy and Regulation, 2018)
This book provides a critical examination of contemporary approaches to environmental regulation in the UK and the European Union. It also explores how regulation has evolved in response to a number of factors, including industrial development and improved scientific knowledge, while considering the radical next steps that need to be taken in response to existing challenges. Developments in Environmental Regulation draws its focus on the effects of risk-based approaches to the environmental regulation of business and industry, including its impact on sustainable economic growth. The book also considers the challenges and potential opportunities that surround the UK's withdrawl, or 'Brexit', from the European Union. This edited collection has been written by a group of highly experienced regulatory specialists whose insightful perspectives on key areas of environmental regulation are situated at the core of this work. This book will appeal to students and academics, policy-makers and environmental practitioners interested in understanding how environmental policy and regulation is applied and how it can be adapted to its political context.